GROWTH PERFORMANCE OF (Oreochromis niloticus) FED DIETARY SUBSTITUTION OF VARIOUS LEVELS OF FISH MEAL WITH SOYBEAN MEAL : Fish meal, soybean meal, inclusion, growth performance, economic performance, Oreochromis niloticus. - OSAYI, S.E.; OKONJI, V.A.; OKOEWA , S.O. (Nigerian Journal of Fisheries, 2024)
This study was carried out to investigate the growth and economic performance of Nile tilapia (Oreochromis niloticus) fed dietary substitution of various levels of fish meal with soybean meal. Fifteen plastic tanks measuring 5x5x4ft (3000L volume) were used for the study for 12 weeks. Juveniles of O. niloticus with mean weights of 3.40±0.06g were stocked in five treatments (T1, T2, T3, T4, and T5). Each treatment was replicated three times. The first treatment (T1) was fed diet with 38.46% fishmeal inclusion, the second treatment (T2), 26.15% fishmeal and 21.69% soybean meal inclusion, the third treatment (T3) 19.23% fishmeal and 29.23% soybean meal inclusion, the fourth treatment (T4) 7.69% fishmeal and 38.69% soybean meal inclusion, and the fifth treatment (T5) was fed diet with 46.15% soybean meal inclusion. The result on growth performance parameters showed that there were no significant differences in the growth of fish amongst treatments (P>0.05). However, the result showed that the fish fed T4 did better in terms of weight gain, relative weight gain, absolute growth rate, and feed conversion ratio. Economically, treatment 4 was more profitable than the other treatments with a net profit value and cost incidence of ₦4925 and ₦72 respectively. This study revealed that T4 had the best result for Nile tilapia without negative effects on growth and economic returns.